Gene expression profiling of lncRNA-HOTAIR and lncRNA-MALAT1 in esophageal cancer: uncovering links to lifestyle factors and diagnostic significance - Vahid Ghorbani; Saeid Ghorbian (Discover Oncology)
Abstract Background Esophageal cancer (EC) is the sixth most common cause of cancer-related deaths globally. Genetic and environmental factors could be affected in EC's onset and development. The potential involvement of lncRNA-HOTAIR and lncRNA-MALAT1 in EC has garnered significant attention in recent studies. Our investigation aimed to examine lncRNA-HOTAIR and lncRNA-MALAT1 gene expression changes in EC patients. Materials and methods Our experimental study focused on 140 patients with malignant EC, comprising 70 paraffin-embedded tumor tissues (FFPE) blocks and 70 FFPE blocks with marginal tissue samples. The relative gene expression levels of lncRNA-HOTAIR and lncRNA-MALAT1 were measured using Real-Time PCR. The data were analyzed using ANOVA and 2−△△CT tests. Results Our analysis revealed a significant increase in tumor expression compared to marginal tissues (P < 0.05). Besides, our research revealed a significant correlation between lncRNA-HOTAIR expression and hot drinks (P = 0.019), metastasis (P = 0.001), and the 5-year survival rate (P = 0.001). We found a significant correlation between lncRNA-MALAT1 expression and alcohol abuse (P = 0.039), hot drinks (P = 0.001), and metastasis (P = 0.039). Conclusion The findings indicate a potential carcinogenic effect of lncRNA-HOTAIR and lncRNA-MALAT1 gene expression alterations in EC patients. Also, studying the lncRNA genes can help us identify biomarkers, emphasizing the significance of early diagnosis and treatment.